1989
DOI: 10.1126/science.2711183
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cis-Acting Promoter Elements in Tissue-Specific Albumin Gene Expression

Abstract: The mouse albumin gene promoter has six closely spaced binding sites for nuclear proteins that are located between the TATA motif and nucleotide position -170. In vitro transcription with liver or spleen nuclear extracts of templates containing either mutated or polymerized albumin promoter elements establishes a hierarchy of the different protein binding sites for tissue-specific albumin gene transcription. The HNF-1 and C/EBP binding sites strongly activate transcription in a tissue-specific manner. The NF-Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
214
1
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(223 citation statements)
references
References 34 publications
5
214
1
1
Order By: Relevance
“…4C, self). Interestingly, however, competition with two distinct C/EBP-binding sites derived from the D site of the albumin promoter (31) or from the A site of the hemopexin promoter (32) could abolish all bands except the one corresponding to complex 3 that appeared therefore to be unique to the COX-2 C/EBP1 site. Since complex 3 was also not supershifted by any of the anti-C/EBP antibodies used (Fig.…”
Section: Dna-protein Interactions On the Cox-2 Promoter Are Onlymentioning
confidence: 99%
“…4C, self). Interestingly, however, competition with two distinct C/EBP-binding sites derived from the D site of the albumin promoter (31) or from the A site of the hemopexin promoter (32) could abolish all bands except the one corresponding to complex 3 that appeared therefore to be unique to the COX-2 C/EBP1 site. Since complex 3 was also not supershifted by any of the anti-C/EBP antibodies used (Fig.…”
Section: Dna-protein Interactions On the Cox-2 Promoter Are Onlymentioning
confidence: 99%
“…These elements have been shown to be the binding sites of a liver-enriched transcription factor, HNF1 (also called LF-B1 and APF) (3-6, 12, 31). Mutations of the AT-rich element cause drastic reduction of liver-specific transcriptional activity both in vitro and in vivo (21,28,33,42), indicating that the AT-rich element and HNF1 play a crucial role in liver-specific promoter activation.…”
mentioning
confidence: 99%
“…Hepatocyte nuclear factor-1 (HNF-1) (Courtois et al 1987), also called APF (Cereghini et al 1988), LFB1 (Hardon et al 1988), HP (Schorpp et al 1988), and A box factor (Maire et al 1989), is a homeo domain-containing protein that acts as a transcriptional activator in vivo and in vitro to regulate the expression of a large group of genes that have the common characteristic of being expressed in hepatocytes . Consistent with the presence of a homeo domain and sequences related to the POU-specific region {Frain et al 1989;Baumhueter et al 1990), HNF-1 has been suggested to play a role in establishing the hepatocyte phenotype.…”
mentioning
confidence: 99%